"Follow the yellow brick road"?: Structural shortcomings in randomized control trials. (March 2020) - Akram-Lodhi, A. Haroon
Abstract: Randomized control trials (RCTs) lie at the heart of the experimental approach to alleviating global poverty, stressing how the mechanics of household choice can be altered to improve welfare. Yet because households are not unified but rather have their own structural characteristics it cannot be assumed that the choice to participate in or the benefits from an intervention are equitably distributed within the household. Similarly, individual choice within and beyond households are constrained by the structure of social-property relations. Thus, choice cannot be isolated from the structures within which members of households live, and which act to constrain agency.